METAPHORIZATION OF TERMS IN POETRY - Kabuljonovna, G.K. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses stylistic features related to use figurative meaning of terms in poetry. Particularly, the metaphorical meaning of terms in poetry is analyzed.